LDLR dysfunction induces LDL accumulation and promotes pulmonary fibrosis. Issue 1 (26th January 2022) - Shi, Xiangguang; Chen, Yahui; Liu, Qingmei; Mei, Xueqian; Liu, Jing; Tang, Yulong; Luo, Ruoyu; Sun, Dayan; Ma, Yanyun; Wu, Wenyu; Tu, Wenzhen; Zhao, Yinhuan; et al.
Abstract: Treatments for pulmonary fibrosis (PF) are ineffective because its molecular pathogenesis and therapeutic targets are unclear. Here, we show that the expression of low‐density lipoprotein receptor (LDLR) was significantly decreased in alveolar type II (ATII) and fibroblast cells, whereas it was increased in endothelial cells from systemic sclerosis‐related PF (SSc‐PF) patients and idiopathic PF (IPF) patients compared with healthy controls. However, the plasma levels of low‐density lipoprotein (LDL) increased in SSc‐PF and IPF patients. The disrupted LDL–LDLR metabolism was also observed in four mouse PF models. Upon bleomycin (BLM) treatment, Ldlr ‐deficient ( Ldlr −/−) mice exhibited remarkably higher LDL levels, abundant apoptosis, increased fibroblast‐like endothelial and ATII cells and significantly earlier and more severe fibrotic response compared to wild‐type mice. In vitro experiments revealed that apoptosis and TGF‐β1 production were induced by LDL, while fibroblast‐like cell accumulation and ET‐1 expression were induced by LDLR knockdown. Treatment of fibroblasts with LDL or culture medium derived from LDL‐pretreated endothelial or epithelial cells led to obvious fibrotic responses in vitro. Similar results were observed after LDLR knockdown operation. These results suggest that disturbed LDL–LDLR metabolism contributes in various ways to the malfunction of endothelial and epithelial cells, and fibroblasts during pulmonary fibrogenesis. In addition, pharmacological restoration of LDLR levels by using a combination of atorvastatin and alirocumab inhibited BLM‐induced LDL elevation, apoptosis, fibroblast‐like cell accumulation and mitigated PF in mice. Therefore, LDL–LDLR may serve as an important mediator in PF, and LDLR enhancing strategies may have beneficial effects on PF. Abstract : Pulmonary fibrosis (PF) is a devastating lung disorder of unknown etiology. We show that disrupted LDL‐LDLR metabolism in human and mouse PF, and then investigated their contributions and underlying mechanisms for PF progression from endothelial/epithelial injury to eventual fibrosis. Pharmacological restoration of LDLR expression can abolish LDL redundancy and prevent PF features.